Abortive regime transition in Egypt: pro-democracy alliance and demand-making framework. Issue 4 (19th May 2018) - Hatab, Shimaa
ABSTRACT: What accounts for the failed transition and restructuring of authoritarianism in Egypt after a fleeting rupture in 2011? How did the dominant statist party lose its iron grip on power? Why did the collapse of the dominant party not bring about significant democratic transformation and generate power-sharing pacts? The article aims to go beyond the question of the importance of either authoritarian resilience or the transition paradigm to offer a two-layered analytical framework based on leverage level and the coherence of pro-democracy forces' demands to account both for the timing of one-party collapse and the consequent dynamics of authoritarian revival. I allow room for complex and strategic interactions between different components of pro-democracy forces and the old ruling class to elucidate the contingent political trajectory after the time of disintegration. When pro-democracy forces maintained their leveraged position and kept a demand-claiming framework unified, they secured a 'cooperative differentiation' position and were able to apply consistent democratization pressure that led to regime breakdown. When they adopted a conformist stance and accommodated their demands to the incumbent regime, they became captive to the interests of old regime holdovers and asserted an 'antagonistic identification' position that hobbled efforts to move towards democratization.